The quadratic equation (k+1)x^2 + (5k - 3)x + 3k = 0 has equal roots. Find the possible values of k

We know the discriminant (b^2 - 4ac) must be equal to zero for an equation to have equal roots (think about the fact that the square root of this is taken in the quadratic equation). So we can form the equation (5k-3)^2 - 4(k+1)(3k) = 0Simplifying this to 13k^2 - 42k + 9 = 0 and factorising to (13k - 3)(k - 3) = 0 (easily done by spotting that 13 is prime), we can see that k = 3 or k = 3/13

Answered by Molly I. Maths tutor

6136 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

What is the difference between a scalar and vector quantity?


integrate (4x^3 +3)(x^4 +3x +16)^2 dx


Differentiate F(x)=(25+v)/v


∫(1 + 3√x + 5x)dx


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences